Spatial–Temporal Characterization of Microplastics in the Surface Water of an Urban Ephemeral River - Andre Felton; Salem Farner; Logan Day; Sue Ellen Gibbs-Huerta; Briaunna Zamarripa; Jeffrey Hutchinson (Microplastics)
Rivers are recognized as major unilateral pathways of microplastic transport between terrestrial and marine ecosystems, yet our understanding of their dispersal patterns over space and through time as they migrate from source to sink is limited. In this study, surface water samples were collected monthly from 12 sites along an urban ephemeral river (Leon Creek) in San Antonio between June 2021 and May 2022 to characterize and evaluate the spatiotemporal distribution of microplastics. Microplastics were found in all sites throughout the monitoring timeframe. The mean abundance of microplastics varied from 3.21 to 26.8 items/L. Surface waters consistently contained microplastics during months of dysconnectivity, suggesting atmospheric deposition as a considerable contributive variable. Contrary to prior studies of perennial systems, ephemeral pools and reaches showed no correlation between MP concentration and season precipitation. Fibers were the most abundant (~87%) morphology followed by foams (7%). This study is the first to report microplastics in ephemeral streams, suggesting that different environmental variables may be responsible for microplastic dynamics in intermittent river and ephemeral stream systems and headwater tributaries of major rivers. As the global extent of IRES systems is projected to increase with continued climate change, understanding such systems’ influence on MP spatial distribution and fluvial transport regimes constitutes valuable information in assessing MP pathways and their fate as a part of the global “Plastisphere” geochemical cycle in the Anthropocene.